2018
DOI: 10.1167/tvst.7.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Widefield and Circumpapillary Circle Scans for Detecting Glaucomatous Neuroretinal Thinning on Optical Coherence Tomography

Abstract: PurposeOur purpose was to compare the effectiveness of detecting progressive retinal nerve fiber layer (RNFL) thickness changes using widefield scans compared to circumpapillary circle scans derived from optic disc volume scans when using a manual region-of-interest (ROI) approach.MethodsIn a prospective observational study, a total of 125 eyes diagnosed clinically with glaucoma or suspected glaucoma that had both widefield (12 × 9 mm) and optic disc (6 × 6 mm) scans obtained at least one year apart were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In patients with glaucoma, studies have shown that reduced macular (Yarmohammadi et al 2017), circumpapillary (Lommatzsch et al 2018) and whole-image VD of 4.5 9 4.5-mm 2 scans on OCTA (Yarmohammadi et al 2016) are significantly associated with disease severity. As a relatively new scan protocol, widefield 12 9 12mm 2 scans are especially valuable in glaucoma diagnostics and management as encompass the macular and circumpapillary vasculature in one single image (Wu et al 2018). Despite the lack of existing literature discussing the repeatability of 12 9 12-mm 2 scans, our results support the longitudinal use of 12 9 12-mm 2 scans in managing patients with diabetic retinopathy and glaucoma.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In patients with glaucoma, studies have shown that reduced macular (Yarmohammadi et al 2017), circumpapillary (Lommatzsch et al 2018) and whole-image VD of 4.5 9 4.5-mm 2 scans on OCTA (Yarmohammadi et al 2016) are significantly associated with disease severity. As a relatively new scan protocol, widefield 12 9 12mm 2 scans are especially valuable in glaucoma diagnostics and management as encompass the macular and circumpapillary vasculature in one single image (Wu et al 2018). Despite the lack of existing literature discussing the repeatability of 12 9 12-mm 2 scans, our results support the longitudinal use of 12 9 12-mm 2 scans in managing patients with diabetic retinopathy and glaucoma.…”
Section: Discussionsupporting
confidence: 54%
“…As a relatively new scan protocol, widefield 12 × 12‐mm 2 scans are especially valuable in glaucoma diagnostics and management as encompass the macular and circumpapillary vasculature in one single image (Wu et al. ). Despite the lack of existing literature discussing the repeatability of 12 × 12‐mm 2 scans, our results support the longitudinal use of 12 × 12‐mm 2 scans in managing patients with diabetic retinopathy and glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, the RNFL thickness using SD-OCT is evaluated from a single circle around the optic disc, but wide-field scan could be more effective in determining the RNFL thickness progression. 34 In addition, wide-field scanning enables the ganglion cell analysis from the fovea together with RNFL measurements to better understand the relation between the loss of macular ganglion cells and their axons. 35 …”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the value of OCT imaging for reducing the sample size requirements in this study was achieved by using the standard global circumpapillary RNFL thickness measure. However, recent studies have revealed how neuroretinal parameters in the macula and posterior pole (outside of the peripapillary region) could also provide important information about disease progression 1014,22,23 that could be exploited to further improve the power to detect a significant treatment effect. Furthermore, analytical methods that limit the evaluation of progression within regions of established glaucomatous damage (to minimize the contribution of measurement variability from non-damaged regions) could further reduce sample size requirements 2326 .…”
Section: Discussionmentioning
confidence: 99%